Brutalist Sheffield. Three Stories of Collective Housing in UK - Feliz Ricoy, Sálvora (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Following the theoretical development of the concept of Street in the Sky by Alison and Peter Smithson, three cases of Brutalist collective housing located in the city of Sheffield (United Kingdom) and developed between 1953-1965 are analyzed: Park Hill Building, Hyde Park Estate and Kelvin flats. These high-density residential sets with a high number of inhabitants sought to reinterpret urban domesticity, fostering social relations around the streets in the sky of these new stacked neighborhoods. After a few decades of prosperity, these examples would derive in controversial situations of neighborhood insecurity, collapse, be demolished or be renovated programmatically and aesthetically. These three strategies show the evolution of three communities and the updating towards new social needs. At present, only Park Hill Building is still standing, in a rehabilitation process in which gentrification tries to combat the enthusiastic obsolescence and unstoppable expiration that these typological supports have demonstrated.